Degradation of per- and polyfluoroalkyl substances (PFAS) in wastewater effluents by photocatalysis for water reuse. (April 2022) - Xia, Chunjie; Lim, Xian; Yang, Haoran; Goodson, Boyd M.; Liu, Jia
Abstract: Wastewater reclamation and reuse have been increasingly practiced in the U.S. as sustainable strategies to meet water demands, particularly in regions threatened by water shortages. However, reuse of wastewater effluents (WEs) as irrigation water (e.g., in agriculture) is challenged by the presence of emerging organic contaminants such as per - and polyfluoroalkyl substances (PFAS), whose presence may result in adverse impacts on crops, soils, aqueous ecosystems, and human health; thus, it is important to remove PFAS in WEs before water reclamation and reuse. In this study, zero-valent iron (Fe 0 ) nanoparticles were investigated for their ability to induce PFAS photocatalytic degradation in WEs under ultraviolet (UV) light. Effective removal of PFAS in WEs was achieved at pH 3.0 in the UV/Fe 0 system. Optimal degradation rates of 90 ± 1%, 88 ± 1%, and 46 ± 2% were obtained for PFNA, PFOS, and PFOA, respectively, each starting from 0.5 μg/L using bare Fe 0 after 2 h. The process is effective without oxygen removal and hence is a low-cost method. The used iron nanoparticles can be recycled by exploiting their magnetic properties. The treatment method can also be successfully applied to the remediation of PFAS-contaminated groundwater and surface water.